Aretological and Educational Implications of (Un)tamed Imagination - Nowakowski, Piotr T. (Paedagogia Christiana, 2026)
The article examines the dual nature of imagination in the context of its aretological and educational implications. Imagination, as an ability supporting intellectual, emotional, and moral development, can inspire creativity, stimulate reflection, and foster positive psychological and social change. However, when left unchecked, it may be a source of cognitive distortions, false memories, escapism, and emotional problems. The author emphasizes the importance of properly guided (self-)education in cultivating a mature and conscious use of imagination, which is particularly relevant in an era of dynamic digital technology development and the ongoing mediatization of life. The article also discusses ways to foster constructive forms of imagination and counteract its negative manifestations.